CERVICAL GUNSHOT INJURY - Gede Andry Nicolas; Heru Sutanto Koerniawan; Raka Janitra; Tjokorda Gde Bagus Mahadewa (Indoscholar, 2018)
The incident of cervical spine injury and cervical spinal cord injury is between 2.0% to 5.0%. The advanced trauma life support (ATLS) stated that a patient with multiple traumas should be assumed to have cervical spine injury especially if the patient loses consciousness when present in the ER. It is stressed that cervical spine injury requires continuous immobilization of the patient’s entire body using a semirigid collar as well as a backboard with tape and straps before and during transfer to a defnitive care facility. The understanding of the mechanism of injury is the most important as the forces transferred are signifcantly diﬀerent causing diﬀerent injuries. A serial case reported by Walter and Adkins found that there was no signifcant diﬀerence between the patients that have a bullet removed from the neck and patients that have a bullet left in the cervical cord. In both cases, there was no improvement to the neurologic outcome. Kupcha recommends doing selective wound management and observation of retained intracanal bullet fragments in a patient with complete lesion. Surgical decompression after the injury is not recommended. We report a case of 14 year old boy who was treated at Sanglah Hospital referred from an out-of-island Type C Hospital with a spinal cord injury - American Spinal Injury Association A (SCI ASIA A) caused by a gunshot wound in the cervical. Surgical decompression and bullet removal was performed as well as fusion stabilization. He is then treated in the intensive care unit for 48 hours with a slight improvement in motoric of upper and lower extremities.